Citizenship Notion Held by Students of Pedagogy - Juan Pablo Fernández-Vega; Héctor Gonzalo Cárcamo-Vásquez (Universidad Nacional, Costa Rica, 2017)
This research aims to recognize the notion of citizenship owned by university students enrolled in the career of History and Geography Teaching at Bío-Bío University (Chile), in 2015. It is based on the methods of education for political, social, and active citizenship from a critical position. It is a descriptive, quantitative approach, with a single study case. A survey aimed at the entire population (census) was used. Thus, it is concluded that the future teaching staff seems to adhere to training methods for social citizenship, corresponding with Marshallian notions of citizenship. However, this notion is not entirely pure, because as reflected in the results, it is importantly present in training for active and critical citizenship.